STUDYING METHODS FOR THE HARMONIOUS DEVELOPMENT OF SOCIAL AND ACADEMIC ABILITIES IN THE EDUCATIONAL PROCESS - Matkarimova Munira Atabekovna (Prospects for innovative technologies in science and education, 2025)
This article analyzes the theoretical foundations and practical mechanisms for the harmonious development of students’ social and academic abilities in the modern educational process. It explores approaches that strengthen social competence, communication culture, collaborative skills, and academic performance. The study highlights the effectiveness of collaborative learning, project-based instruction, differentiated approaches, competency-oriented tasks, and reflective activities.